ANALISIS BIAYA-VOLUME-LABA JANGKA PANJANG - Bambang Sudibyo (Journal of Indonesian Economy and Business (JIEB), 1986)
No abstract was detected.Sudibyo, Bambang. (1986). Analisis Biaya-Volume-Laba Jangka Panjang. Jurnal Ekonomi dan Bisnis Indonesia [Journal of Indonesian Economy and Business], 1. 21-40.